Musicality and psychoanalysis - Dos Santos, Bruno Gonçalves; Dionísio, Gustavo Henrique [UNESP] (My University, 2018)
Following the perspective of Freud and Lacan, this work theoretically discusses the musicality and its implications in the psychic constitution of the subject, considering the peculiarities that occur in the dynamics of sound signifiers. According to our developments, musicality maintains in itself the primordial relation of the signifier in which there is no forclusion (Verwerfung) the Real, evidencing a process of significant chaining even before the production of imaginary signification. In this sense, musicality is taken as producing significant sonorous relation that maintains in itself the elementarity of the Real, demonstrating a way of intervention in the clinic by way of musicality for the production of sound discourse, even if without meaning, that gives ways to the subject of treatment of their enjoyment. In order to substantiate this hypothesis, we discuss the Invocative Pulsion in relation to the primordial Other, and the voice as the object a, as a phenomenon other than sound.
Musicalité et psychanalyse
Musicalidade e psicanálise
Keywords: Forclusion; Invocating pulse; Musicality; Psychoanalysis and music; Voice